Forming of content of electronic textbooks of the system of vocational education - Yurzhenko, Volodymyr (Professional Pedagogics, 2014)
The problem of using the latest technology mapping information through 3D-environment as a priority for educational policy in the field of vocational training. Presents the essence of the revision approaches in shaping the content and structure of e-books using the whole arsenal of possibilities of modern information and communication technologies, especially three-dimensional maps. Analyzed the need for a new generation of electronic books that need to use different ways of action on human organs of perception – sound, color, placement of elements display the contents against the monitor screen, dynamic content elements, stereoscopic 3D-images that stimulate the perception of educational information to students VET more effective use of class time. Grounded specific issues of 3D-content, and are some disadvantages of using these teaching methods, and possible ways of reducing this negative impact. Definitely the possibilities of using 3D-content along with some elements of Neuro Linguistic Programming (NLP) in the learning environment of e-books, allowing thus a qualitatively reproduce the elements of visual images in the learning process.